2005
DOI: 10.1002/cncr.21349
|View full text |Cite
|
Sign up to set email alerts
|

Reflex high-risk human papillomavirus DNA testing (Hybrid Capture 2) of bloody ThinPrep specimens with atypical squamous cells of undetermined significance interpretation

Abstract: The pretreatment of bloody specimens with GAA did not appear to significantly affect high-risk HPV DNA testing in specimens with an ASCUS interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…These findings would seem to indicate low cellular yields on specimen collection; in particular, peri/postmenopausal patients and those who had received radiation/chemotherapy. The issue of a glacial acetic acid wash and its effect on HPV analysis has been addressed in the literature with some reporting no effect and others false‐positive HPV results. This issue requires further study and is not in the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings would seem to indicate low cellular yields on specimen collection; in particular, peri/postmenopausal patients and those who had received radiation/chemotherapy. The issue of a glacial acetic acid wash and its effect on HPV analysis has been addressed in the literature with some reporting no effect and others false‐positive HPV results. This issue requires further study and is not in the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, specimen carryover (potentiated by either form of automation) may be of concern to both laboratorians and cytopathologists. Moreover, previous data (8)(9)(10) suggest that performance characteristics of DNA-based HPV modalities may be affected by glacial acetic acid (GAA) treatment of liquid-based cytology collections. The purpose of this investigation was to assess such preanalytical concerns inherent to the performance of the Aptima HPV.…”
Section: Etection Of High-risk Human Papillomavirus (Hpv) E6/e7mentioning
confidence: 99%
“…A few studies, typically focused on hybrid capture technology (H c 2; Qiagen/Digene, Gaithersburg, MD), have been conflicting on the potential effect of GAA on HPV DNA detection (1,6). In addition to oligonucleotide probes specific for 14 high-risk HPV types (provided in three reagent mixtures), the Cervista HPV HR (Hologic/Third Wave Technologies, Madison, WI) possesses an oligonucleotide probe to assess relative DNA content.…”
mentioning
confidence: 99%
“…While this paradigm has procured a high percentage of newly satisfactory Pap smear analyses and has increased detection of significant gynecological lesions (1,2,6,11), recent data have revealed that GAA treatment increases false-positive diagnoses of atypical endocervical cells (3). A few studies, typically focused on hybrid capture technology (H c 2; Qiagen/Digene, Gaithersburg, MD), have been conflicting on the potential effect of GAA on HPV DNA detection (1,6).…”
mentioning
confidence: 99%